Pancreatic Pseudocyst of Gastrohepatic Ligament: A Case Report and Review of Management - Goyal, Sunder; Raju, Rajesh; Yadav, Sidhartha (JOP. Journal of the Pancreas, 2012)
Context Pancreatic pseudocyst of gastrohepatic or hepatoduodenal ligament and of liver is rare entity. Probably, pancreatic pseudocyst ascends via these ligaments to liver due to complex attachment of peritoneum. Very few cases have been reported in literature. Case report Hereby, we report a case of pancreatic pseudocyst of hepatoduodenal ligament in patient who presented with pain and lump in epigastric region. Conclusion This is an extrapancreatic extension of pancreatic pseudocyst and a high suspicion of this cyst (gastrohepatic ligament cyst) should be kept in mind as differential diagnosis of epigastric mass. Image: Excised pancreatic pseudocyst of gastrohepatic ligament.